Financial Sector Reform and Monetary Policy in the Netherlands - Hilbers, Paul (IMF Working Papers; Working Paper ;, 1998)
Financial sector liberalization, both domestic and in cross-border transactions, was a major force behind the gradual move to indirect controls and the shift toward full reliance on exchange rate targeting in the Netherlands. This paper analyzes the different steps in this process, discusses the main arguments behind the gradual approach, and draws lessons for other countries involved in this process. The paper argues that reforms in the financial sector, liberalization of the capital account, adjustments in supervision and regulation, and modernization of monetary management are strongly interrelated and should be part of a comprehensive reform strategy.